The effect of one year treatment with GLP1-RA, SGLT2i and their combination on plasma levels of oxidative and antioxidative biomarkers. (14th October 2021) - Ikonomidis, I; Thymis, J; Pavlidis, G; Birba, D; Kalogeris, A; Kousathana, F; Kountouri, A; Korakas, E; Kostelli, G; Triantafyllou, C; Triantafyllidi, H; Andreadou, I; et al.
Abstract: Background/Introduction: Biomarkers of oxidative stress burden are found increased in Type-2 diabetes mellitus (T2DM) patients. An imbalance between oxidative and antioxidative plasma factors is implicated in the pathway of cardiovascular disease in diabetics. Novel antidiabetic agents with cardioprotective effects are glucagon like peptide-1 receptor agonists (GLP1-RA) and sodium-glucose cotransporter-2 inhibitors (SGLT-2i). Purpose: We investigated the effect of liraglutide (GLP1-RA), empagliflozin (SGLT-2i) and their combination on plasma levels of oxidative and antioxidative factors. Methods: A hundred-sixty T2DM patients were randomly assigned and received: a) insulin (n=40), b) liraglutide (n=40), c) empagliflozin (n=40) and d) the combination liraglutide and empagliflozin (n=40) for 1 year. We measured at baseline and after 1 year of treatment the following antioxidative markers: a) Reducing Power (RP), b) 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), c) Total Antioxidant Capacity (TAC) and also Thiobarbituric acid reactive substances (TBARS) as a marker of oxidative burden. Results: After 1 year of treatment all subjects achieved successful glycemic regulation, as estimated by Hemoglobin A1c (HbA1c) levels (8±0.5 vs 6.65±0.5, p<0.05). Patients on the combination GLP1-RA + SGLT2i displayed greater reduction of TBARS (8.66±0.42 μmol/l vs 7.92±0.35 μmol/l, p<0.05) and increase of ABTS (17.49 ±0.63 mmol/l vs 19.14 ±0.64 mmol/l, p<0.05) compared with insulin-treated participants (8.85±0.41 μmol/l vs 8.83±0.44 μmol/l and 17.07 ±0.58 mmol/l vs 17.22 ±0.49 mmol/l, p=NS respectively). Patients treated on GLP1-RA or SGLT2i separately showed the same improving trend with the combination group in the abovementioned biomarkers but the changes were not so prominent. In the insulin group worsening of TAC was also noticed (0.92±0.02 mmol/l vs 0.89±0.01 mmol/l, p<0.05). In the other biomarkers nonsignificant changes were observed for all groups. Furthermore the absolute change of HbA1c was correlated with the relative change of TBARS (r=0.419, p<0.05) Conclusion: One year treatment with the GLP1-RA liraglutide and SGLT2i empagliflozin resulted in improvement of plasma levels of oxidative and antioxidative biomarkers compared to administration of insulin and the changes were more outstanding in patients that received the combination of GLP1-RA and SGLT2i, despite similar glycemic regulation in all participants. Thus the favorable cardiovascular effects of these novel factors may be partly explained by alterations in equilibrium between oxidative and antioxidative circulating biomarkers. FUNDunding Acknowledgement: Type of funding sources: None.